2017
DOI: 10.3389/fnins.2017.00447
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Sympathoexcitation Was Associated with Paraventricular Hypothalamic Phosphorylation of Synaptic CaMKIIα and MAPK/ErK

Abstract: Systemic administration of adrenergic agonist (Isoproterenol; ISOP) is known to facilitate cardiovascular changes associated with heart failure through an upregulation of cardiac toll-like receptor 4 (TLR4). Furthermore, previous studies have shown that cardiac tissue-specific deletion of TLR4 protects the heart against such damage. Since the autonomic regulation of systemic cardiovascular function originates from pre-autonomic sympathetic centers in the brain, it is unclear how a systemically driven sympathet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Besides the RVLM, other brain regions have been also described as potential contributors to sympathoexcitation in HF (8,78,119). Indeed, the nucleus of the tractus solitarius (NTS), which represents the primary central integration site for peripheral chemoreceptor and baroreceptor activity, has been identified as a master regulator of chemoreflex and baroreflex function (36).…”
Section: Central Mechanisms Contributing To Autonomic Dysfunction In Hfmentioning
confidence: 99%
“…Besides the RVLM, other brain regions have been also described as potential contributors to sympathoexcitation in HF (8,78,119). Indeed, the nucleus of the tractus solitarius (NTS), which represents the primary central integration site for peripheral chemoreceptor and baroreceptor activity, has been identified as a master regulator of chemoreflex and baroreflex function (36).…”
Section: Central Mechanisms Contributing To Autonomic Dysfunction In Hfmentioning
confidence: 99%
“…MAPK, including p44/42 MAPK, JNK, and p38 MAPK as the major family members, plays pivotal roles in heart failure [ 53 ] and hypertension [ 54 ]. Recently, it was reported that phosphorylation of the MAPK within the PVN contributes to excessive RSNA, and the p44/42 MAPK inhibitor, PD-98059, micro-injected in the PVN significantly reduces RSNA in both heart failure [ 26 ] and ANG II-induced hypertensive rats [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…MAPK/ERK was more highly expressed in the PVN of SHR by the fourth week [36]. Ang II-mediated activation of MAPK/ERK increased vesicular release of presynaptic glutamate in the brain [37].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Ang II-induced sympathoexcitation in the PVN, may involve the alteration of excitatory (glutamate and cathecolamines) and inhibitory (GABA) neurotransmitter systems through ROS-ERK signaling pathways [38]. Recent studies demonstrated that ERK signaling in PVN can modulate SNA to affect cardiovascular function [36,39]. For instance, the anti-obesity effect of nesfatin-1 is mediated by hypothalamic ERK-dependent sympathoexcitation in obese animals [39].…”
Section: Discussionmentioning
confidence: 99%